Molten salt strategy to synthesize alkali metal-doped Co9S8 nanoparticles embedded, N, S co-doped mesoporous carbon as hydrogen evolution electrocatalyst. (28th February 2020) - Yu, Huan; Sun, Xiaoying; Tang, Duihai; Huang, Yuan; Zhang, Wenting; Miao, Sijia; Qiao, Zhen-An; Wang, Jianjun; Zhao, Zhen
Abstract: A molten salt strategy was proposed to prepare a series of electrocatalysts for hydrogen evolution reaction (HER) with salts as templates, which consisted of Co9 S8 nanoparticles (NPs) and N, S co-doped mesoporous carbons. The porosities, heteroatoms contents, and crystalline structures of the final electrocatalysts were determined by the types of salts and the calcining temperatures. When KCl/NaCl, KCl/LiCl, and NaCl/CaCl2 were adopted as the molten salts, Co9 S8 NPs embedded, N, S co-doped carbons were obtained. However, when CaCl2 and ZnCl2 were used as the molten salts, Co9 S8 could not be synthesized. The characterization results exhibited that alkali metal atoms could be introduced in the lattices of Co9 S8 . The combination of experimental and theoretical results revealed that Na and K atoms doping improved the electrocatalytic performance for HER. GTCo900-KCl/NaCl possessed the best HER activity, delivering a current density of 10 mA cm −2 at 54 mV in acidic media, 142 mV in neutral media, and 103 mV in alkaline media. Highlights: Co9 S8 NPs entrapped, N, S co-doped carbons were prepared via molten salt methods. The calcining temperatures and types of salts affect the mesoporous structures. Na and K atoms doping improve the electrocatalytic performance for HER.